2006
DOI: 10.1111/j.1464-410x.2006.06286.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sexual Assessment Monitor, a diagnostic device used to electronically quantify ejaculatory latency time: findings from three studies

Abstract: OBJECTIVETo validate the Sexual Assessment Monitor (SAM), a novel apparatus designed to collect electronic data on ejaculatory latency time (ELT) for diagnosing premature ejaculation (PE), and for accurately measuring treatment outcomes in clinical trials. PATIENTS, SUBJECTS AND METHODSMen with PE, and healthy volunteers aged 18-75 years, were enrolled in three openlabel studies, conducted in the UK. The SAM, which consists of a control box with two front attachments, a vibrator and sensor, was attached to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Laboratory studies of ejaculatory dysfunction may be simplified by the use of the Sexual Assessment Monitor (SAM), an electronic data collector which comprises a vibrator to induce ejaculation and a sensor to measure time-to-erection and IELT by the detection of ejaculatory pulses, but the role of such devices in large at-home Phase III clinical trials is limited. [69] Recent normative IELT data supports earlier suggestions by several authors that intravaginal ejaculatory latency times (IELTs) of less than 1 minute or less than 2 minutes be regarded as cut-points for inclusion in a clinical trial. [92740] Subjective patient reported outcomes (PROs) of ejaculatory control, sexual satisfaction and bother/distress are important additional efficacy endpoints and can be evaluated using validated patient reported outcome instruments.…”
Section: Pe Drug Trial Designsupporting
confidence: 67%
“…Laboratory studies of ejaculatory dysfunction may be simplified by the use of the Sexual Assessment Monitor (SAM), an electronic data collector which comprises a vibrator to induce ejaculation and a sensor to measure time-to-erection and IELT by the detection of ejaculatory pulses, but the role of such devices in large at-home Phase III clinical trials is limited. [69] Recent normative IELT data supports earlier suggestions by several authors that intravaginal ejaculatory latency times (IELTs) of less than 1 minute or less than 2 minutes be regarded as cut-points for inclusion in a clinical trial. [92740] Subjective patient reported outcomes (PROs) of ejaculatory control, sexual satisfaction and bother/distress are important additional efficacy endpoints and can be evaluated using validated patient reported outcome instruments.…”
Section: Pe Drug Trial Designsupporting
confidence: 67%
“…The IELT, AELT, OELT, and MELT can be estimated by the subject or can be measured with a stopwatch operated by the female partner, is expressed in seconds or minutes, and in cases of anteportal ejaculation, is equal to zero. In laboratory studies of ejaculatory dysfunction, MELT can be measured with the Sexual Assessment Monitor, an electronic data collector that comprises a vibrator to induce ejaculation and a sensor to measure time‐to‐erection and MELT by the detection of ejaculatory pelvic floor muscle contractions [31].…”
Section: Baseline Ejaculatory Latency Time (Elt)mentioning
confidence: 99%
“…A novel apparatus has been designed and validated to collect electronic data on IELT, called the Sexual Assessment Monitor (SAM). Dinsmore et al 56 showed that the SAM is able to measure effectively and safely the time to ejaculation from the start of vibration in healthy volunteers and men with PE. The authors concluded that the SAM has the potential to become the gold standard for the diagnosis of PE, as well as in the design of clinical trials.…”
Section: Pathophysiology Of Premature Ejaculationmentioning
confidence: 98%